2012
DOI: 10.1523/jneurosci.4201-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Alpha/Beta Oscillations Indicate Inhibition of Interfering Visual Memories

Abstract: Selective retrieval of a specific target memory often leads to the forgetting of related but irrelevant memories. Current cognitive theory states that such retrieval-induced forgetting arises due to inhibition of competing memory traces. To date, however, direct neural evidence for this claim has not been forthcoming. Studies on selective attention suggest that cortical inhibition is mediated by increased brain oscillatory activity in the alpha/beta frequency band. The present study, testing 18 human subjects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
107
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 51 publications
(95 reference statements)
19
107
2
Order By: Relevance
“…The current time-frequency results in combination with previous research indicate that neural oscillations are a useful tool for studying the temporal dynamics of encoding retrieval overlap (Jafarpour et al, 2014;Staresina et al, 2016;Staudigl & Hanslmayr, 2013;Staudigl et al, 2015;Waldhauser et al, 2012;Waldhauser et al, 2016). Burke et al (2013), for example, found that high gamma activity (44-100Hz) during successful encoding of information is also observed in similar brain areas during the memory test phase in which previously studied items need to be recalled.…”
Section: Discussionsupporting
confidence: 70%
“…The current time-frequency results in combination with previous research indicate that neural oscillations are a useful tool for studying the temporal dynamics of encoding retrieval overlap (Jafarpour et al, 2014;Staresina et al, 2016;Staudigl & Hanslmayr, 2013;Staudigl et al, 2015;Waldhauser et al, 2012;Waldhauser et al, 2016). Burke et al (2013), for example, found that high gamma activity (44-100Hz) during successful encoding of information is also observed in similar brain areas during the memory test phase in which previously studied items need to be recalled.…”
Section: Discussionsupporting
confidence: 70%
“…First, it has been well established that memory for pictures is better than memory for words (Durso & O'Sullivan, 1983;Gehring, Toglia, & Kimble, 1976;Hockley, 2008;Juola, Taylor, & Young, 1974;Madigan, 1974;Nelson, Reed, & McEvoy, 1977;Nelson, Reed, & Walling, 1976;Paivio & Csapo, 1973;Paivio, Rogers, & Smythe, 1968;Snodgrass & Burns, 1978;Snodgrass, Volvovitz, & Walfish, 1972;Snodgrass, Wasser, Finkelstein, & Goldberg, 1974), despite considerably more of the existing research on long-term memory having been conducted using verbal stimuli (Palmer, 1999). This led Maxcey and Woodman to predict that memory for pictoral stimuli in visual long-term memory would be immune to forgetting effects shown with words (e.g., retrieval-induced forgetting) and thus unimpaired following recognition practice (see also Ciranni & Shimamura, 1999;Fan & Turk-Browne, 2013;Shaw, Bjork, & Handal, 1995;Waldhauser, Johansson, & Hanslmayr, 2012). Contrary to their prediction, practice recognizing pictoral stimuli led to the forgetting of related stimuli.…”
Section: Are Practiced)mentioning
confidence: 97%
“…Alpha and beta power decreases have also been linked to successful episodic memory retrieval in several studies (Duzel et al, 2010; Hanslmayr et al, 2012 for reviews). Alpha and beta power decreases as the number of retrieved items increases and varies spatially across the scalp according to the type of perceptual features associated with prior encoded events (Khader & Rosler, 2011; Waldhauser, Braun, & Hanslmayr, 2016; Waldhauser, Johansson, & Hanslmayr, 2012). …”
Section: Introductionmentioning
confidence: 99%